Storing keV negative ions for hours: Lifetime measurements in new time domains. (August 2015) - Kaminska, M; Bäckström, E; Hanstorpt, D; Hole, O M; Nascimento, R F; Blom, M; Björkhage, M; Källberg, A; Löfgren, P; Reinhed, P; Rosèn, S; Thomas, R D; et al.
Synopsis: We have used one of the cryogenic ion storage rings of DESIREE to measure the lifetime of the 2 P°1/2 level in the sulfur anion to be 503 ± 43 seconds. This is orders of magnitude longer than any previously measured lifetime in a negatively charged ion.